Strengthening Leadership Communication Based on Neuro-Linguistic Programming (NLP) for Teachers and School Principals - Maulia Depriya Kembara; Rita Anggorowati; Atep Sujana; Nandang Rusmana; Leni Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Despite the critical role of leadership communication in educational transformation, many teachers and principals still experience limitations in empathetic and strategic communication, resulting in suboptimal collaboration and innovation. This study aims to evaluate the effectiveness of Neuro-Linguistic Programming (NLP)-based training in enhancing leadership communication competencies among educational practitioners. The research employed a quasi-experimental design with a pre-test–post-test approach involving 39 participants, including teachers, school leaders, and postgraduate students. Data were collected using validated instruments measuring authentic leadership, NLP-based communication skills, and teacher performance, supported by reflective writings and peer feedback. Quantitative data were analyzed using paired-samples t-tests, while qualitative data were examined through thematic analysis. The results indicate a significant improvement in participants’ communication competencies across cognitive, behavioral, and affective domains. Participants also demonstrated the ability to apply key NLP techniques, such as rapport-building and active listening, in professional contexts. This study implies that NLP-based training provides an effective and practical approach for strengthening leadership communication and supporting professional development in educational settings.